Nigeria and the challenges of terrorism in the 21st century - Onome Alex Onohworemu; Abraham. O. Egbadju (Department of Accounting Universitas PGRI Yogyakarta, 2025)
This study examined terrorism in Nigeria between 2010 and 2023, focusing on its root causes, evolution, and effects on national development. Using a historical research design and qualitative analysis of documentaries, this study applies relative deprivation theory to explain how systemic deprivation, unemployment, and state failures perpetuate violence. Findings reveal that political competition, regional disparities, poverty, inequality, corruption, and weak governance have fueled exclusion and marginalization, which in turn breed anger, distrust, and violent extremism. Neo-patrimonial practices and ineffective leadership further undermine unity and development. The study concluded that terrorism in Nigeria extends beyond groups like Boko Haram, as past communal conflicts and socio-economic grievances contribute significantly to nationwide insecurity. To address these challenges, the study recommended tackling marginalization, poverty, inequality, religious extremism, and weak institutions. Strategic investments in youth, healthcare, and education, effective resource allocation, and reforms in governance and security are essential for rebuilding communities, mitigating external influences, and ensuring sustainable peace and development.